(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2021)
The aim of the analysis is to present the level of intercultural competence of language teachers in Novi Pazar primary and secondary schools. In a survey conducted in October 2020/21. 35 language teachers participated in the year. The research was conducted by surveying language teachers, where the survey consisted of closed and open questions, and examined the attitudes of language teachers about intercultural teaching, the importance of acquiring intercultural competence through language teaching, the need for intercultural competence and students and teachers, the development of intercultural sensitivity and perception their role as mediators between the party and the mother tongue culture. We approached the presentation of the obtained data with quantitative-qualitative analysis, on the basis of which we confirmed the hypothesis that intercultural competence is an indispensable construct of language teaching, and equally important for students and teachers.